Salvage percutaneous high-dose-rate brachyablation after stereotactic body radiation therapy for early-stage non-small cell lung cancer - Wu, Trudy C.; Lee, Alan; Suh, Robert; Oughourlian, Talia C.; Abtin, Fereidoun; Hagio, Mary Ann; Park, Sang-June; Chang, Albert J.; Moghanaki, Drew (Journal of Contemporary Brachytherapy, 2024)
Patients with primary tumor progression after stereotactic body radiation therapy (SBRT) for stage I non-small cell lung cancer (NSCLC) have a second chance at complete tumor eradication with salvage local therapies, including lung resection, repeat course of SBRT, and percutaneous ablative therapies. In this paper, we presented our institution’s initial experience with percutaneous high-dose-rate (HDR) brachyablation for a relapsed stage I NSCLC that had been treated with SBRT 4.3 years earlier. Lung tumor measuring approximately 5 cm in maximum tumor dimension at the time of relapse was histopathologically confirmed to be persistent squamous cell carcinoma, and successfully treated with a single fraction of 24 Gy with HDR brachyablation. Treatment was delivered via two percutaneous catheters inserted under CT-guidance, and treated in less than 20 minutes. The patient was discharged home later the same day without the need for a chest tube, and has been monitored with serial surveillance scans every 3 to 6 months without evidence of further lung cancer progression or complications at 2.8 years post-HDR brachyablation procedure and 7.8 years after initial SBRT.